Hubungan Paritas dan Umur Kehamilan Terhadap Kejadian Anemia pada Ibu Hamil: The Relationship Between Parity and Gestational Age with the Incidence of Anemia in Pregnant Women - Ni Kadek Gina Pramitayani; Ni Nyoman Ayu Desy Sekarini; Putu Irma Pratiwi (Universitas Ngudi waluyo, 2026)
Anemia during pregnancy remains a public health problem that carries the risk of increasing maternal and neonatal morbidity, including preterm birth, low birth weight, and other obstetric complications. Parity and gestational age are thought to contribute to the incidence of anemia, but previous studies have shown inconsistent findings. This study aims to analyze the relationship between parity and gestational age with the incidence of anemia in pregnant women. This study used an analytical observational design with a cross-sectional approach and utilized secondary data from the antenatal care (ANC) service register. The study population was all pregnant women registered at the TPMB